87.3k views
0 votes
Multiply and simplify (x-2) (2x+1)

User Vanette
by
4.9k points

2 Answers

0 votes

Answer:

2x2−3x−2

Explanation:

Simplify

(x−2)(2x+1)

=(x+−2)(2x+1)

=(x)(2x)+(x)(1)+(−2)(2x)+(−2)(1)

=2x2+x−4x−2

User Michael Slade
by
4.7k points
4 votes

Answer:

2x² - 3x - 2

Explanation:

Given

(x - 2)(2x + 1)

Each term in the second factor is multiplied by each term in the first factor, that is

x(2x + 1) - 2(2x + 1) ← distribute both parenthesis

= 2x² + x - 4x - 2 ← collect like terms

= 2x² - 3x - 2

User DeepNightTwo
by
5.0k points